Gap junction Delta-2b (gjd2b/Cx35.1) depletion causes hyperopia and visual-motor deficiencies in the zebrafish - Brown-Panton, Cherie A.; Sabour, Shiva; Zoidl, Georg S. O.; Zoidl, Christiane; Tabatabaei, Nima; Zoidl, Georg R. (Frontiers in Cell and Developmental Biology, 2023)
The zebrafish is a powerful model to investigate the developmental roles of electrical synapses because many signaling pathways that regulate the development of the nervous system are highly conserved from fish to humans. Here, we provide evidence linking the mammalian connexin-36 (Cx36) ortholog gjd2b/Cx35.1, a major component of electrical synapses in the zebrafish, with a refractive error in the context of morphological, molecular, and behavioral changes of zebrafish larvae. Two abnormalities were identified. The optical coherence tomography analysis of the adult retina confirmed changes to the refractive properties caused by eye axial length reduction, leading to hyperopic shifts. The gjd2b/Cx35.1 depletion was also correlated with morphological changes to the head and body ratios in larvae. The differential expression of Wnt/ß-catenin signaling genes, connexins, and dopamine receptors suggested a contribution to the observed phenotypic differences. The alteration of visual-motor behavioral responses to abrupt light transitions was aggravated in larvae, providing evidence that cone photoreceptor cell activity was enhanced when gjd2b/Cx35.1 was depleted. The visual disturbances were reversed under low light conditions in gjd2b−/−/Cx35.1−/− larvae. Since qRT-PCR data demonstrated that two rhodopsin genes were downregulated, we speculated that rod photoreceptor cells in gjd2b/Cx35.1−/− larvae were less sensitive to bright light transitions, thus providing additional evidence that a cone-mediated process caused the VMR light-ON hyperactivity after losing Cx35.1 expression. Together, this study provides evidence for the role of gjd2b/Cx35.1 in the development of the visual system and visually guided behaviors.